Global governance, economy and law : waiting for justice - Mendes, Errol (Routledge studies in international law ;, 2003)
Using history, political science, law and economics, this book examines important institutions of global governance including the United Nations, the World Trade Organization, the International Monetary Fund and the World Bank.